FORMULATION OF VILLAGE HEAD DISCRETION POLICY (Policy Formulation Study in Sumber Lele Village and Kebon Agung Village) - yanto, supri; yuswadi, hary (Universitas Muhammadiyah Jember, 2020)
This study The purpose of this study is to find out the process of formulating discretionary policies carried out by the village head. The method used in this study is a qualitative study method. The type of study used in this study is the type of descriptive study. Based on the results of the study it was concluded that the process of discretion policy formulation carried out by the village head was still not optimal, this is due to the low capacity of the village head as the main actor in the discretion policy formulation process. This can be seen from the lack of ability in discretionary policies, thus affecting the monopoly in the process of formulating discretionary and undemocratic policies, as happened in Kebon Agung Village. Whereas in Sumber Lele Village the conditions are better, because it has involved the parties (stakeholders). Although the parties (stakeholders) which is involved does not yet reflect aspects of democracy and representation, because of the parties (stakeholders) only community and religious leaders were involved.